Progress and prospects of C4 trait engineering in plants. (13th July 2022) - Pradhan, B.; Panda, D.; Bishi, S. K.; Chakraborty, K.; Muthusamy, S. K.; Lenka, S. K.
Abstract: Incorporating C4 photosynthetic traits into C3 crops is a rational approach for sustaining future demands for crop productivity. Using classical plant breeding, engineering this complex trait is unlikely to achieve its target. Therefore, it is critical and timely to implement novel biotechnological crop improvement strategies to accomplish this goal. However, a fundamental understanding of C3, C4, and C3 –C4 intermediate metabolism is crucial for the targeted use of biotechnological tools. This review assesses recent progress towards engineering C4 photosynthetic traits in C3 crops. We also discuss lessons learned from successes and failures of recent genetic engineering attempts in C3 crops, highlighting the pros and cons of using rice as a model plant for short‐, medium‐ and long‐term goals of genetic engineering. This review provides an integrated approach towards engineering improved photosynthetic efficiency in C3 crops for sustaining food, fibre and fuel production around the globe. Abstract : This article presents a roadmap for improving photosynthetic efficiency in staple crops based on the current experimental advances.